Numerical Study of B-Screw Ship Propeller Performance: Effect of Tubercle Leading Edge - Mohammad Danil Arifin; Frengki Mohamad Felayati (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2021)
Various attempts to modify the ship's propeller have been made to improve performance as a propulsion component. This paper analyzes the effect of modification of the B-Series propeller by adopting a whale fin shape (Humpback Whale). Also, it analyzes the flow in the propeller before (standard) and after modification. Modifications are made to the leading edge, which is called the tubercle leading edge (TLE). It adds and subtracts sections with a wavelength of 0.2R and amplitude of 2.5% of the chord section length in the propeller leading edge. The numerical study is used using CFD on different J values (0.2, 0.4, and 0.6). It was found that the modification of TLE has a less significant effect on performance. Instead, it decreased at a low J value (0.2). Meanwhile, the largest decrease was at a high J value (0.6), namely up to 10.4% for thrust, 4.3% for torque, and 6.4% for efficiency. Whereas at J=0.4, the torque increases only 0.4%, and the torque and thrust decrease, although less significant. The flow analysis indicates that the shape of the TLE provides a decrease in pressure. However, on the positive side, this modification provides a reduction in noise on the propeller surface.